Pathogenicity and host-interacting mechanisms of enterogenic Enterobacter cancerogenus in silkworm - Luo, Meng; Lai, Linhui; Wu, Zailin; Ren, Xiaoli; Zhao, Jiacheng; Liu, Hongmei; Long, Yaohang (Frontiers in Microbiology, 2025)
IntroductionEnterobacter cancerogenus (E. cancerogenus) is a facultative anaerobic, gram-negative bacterium that can be utilized for the biological control of pests. However, the molecular mechanisms underlying the pathogenicity of E. cancerogenus in insect hosts remain largely unexplored.MethodsIn this study, the Bombyx mori model was employed to investigate the pathogenicity of E. cancerogenus strain ECL7, a bacterium pathogenic to silkworms, through whole-genome sequencing, 16S rDNA sequencing, and transcriptome analysis.ResultsThe results revealed that ECL7 harbors virulence genes associated with biofilm formation, adhesion, type III secretion system (T3SS), type VI secretion system (T6SS), and other factors, which collectively lead to damage to the peritrophic matrix (PM) and intestinal epithelial cells of the silkworm midgut following infection, and reduced silkworm larval survival rates and inhibited their growth and development. Additionally, ECL7 infection altered the composition and abundance of intestinal microorganisms, with Enterobacteriaceae and Enterobacteriales becoming dominant species. ECL7 also stimulated the expression of genes related to the Toll and IMD immune signaling pathways, resulting in the upregulation of antimicrobial peptide–related differentially expressed genes (DEGs). Furthermore, transcriptomic analysis revealed an upregulation of DEGs associated with oxidative stress in response to ECL7 infection.DiscussionThis study provides valuable insights into the molecular mechanisms underlying the interaction between E. cancerogenus and silkworms. The findings contribute to the prevention and control of infections caused by this bacterium in sericulture production and offer novel ideas for the potential application of E. cancerogenus in pest biological control.